Implementasi Nilai-Nilai Kearifan Lokal dalam Pembelajaran Sejarah di Madrasah Aliyah Tahfizhil Quran - Kaldianus, Retno; Pulung Sumantri; Aditya Darma (Medan Resource Center, 2023)
This research aims to describe the implementation of local wisdom in history education, analyze the students' understanding at Madrasah Aliyah Tahfizhil Quran towards history learning, and identify the challenges faced by teachers in instilling local wisdom in students at Madrasah Aliyah Tahfizhil Quran. The cultivation of local wisdom is crucial as a means for students to appreciate culture. The method used is qualitative with a case study approach, focusing further on specific social aspects causing the problem. Data collection techniques include observation, interviews, and documentation. Data analysis employs interaction analysis consisting of data collection, data reduction, data presentation, and conclusion drawing. The research findings indicate that 1) the teachers' implementation of local wisdom in history education is mainly through developing regionally related learning activities outside of formal curriculum sessions. 2) The students have effectively implemented local wisdom values, encompassing ethics, aesthetics, religious, and social values.